HUBUNGAN ANTARA MOTIVASI PERAWAT KAMAR OPERASI DENGAN KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI SAAT MELAKUKAN PEMBEDAHAN DIKAMAR OPERASI - Lusinda, Riko Citra (STIKES Widyagama Husada, 2025)
People in healthcare facilities are at high risk of exposure to infection, especially operating room staff, delivery room staff, inpatient ward staff, postpartum ward staff, and others. One of the efforts made by hospitals to avoid the risk of exposure to infection is to provide personal protective equipment (PPE). The objective of this study was to determine the relationship between nurses' motivation to use PPE in the operating rooms of Dr. Saiful Anwar Regional General Hospital in East Java Province. This study used a cross-sectional correlational design. The sampling technique used non-probability sampling with total sampling, sampling 41 operating room nurses. The research instruments were questionnaires and observation sheets. Data analysis used the Spearman's rank correlation test. The data analysis showed that 36 (87.8%) operating room nurses had moderate motivation, and 12.2% had high motivation. A total of 13 (31.7%) operating room nurses were classified as non-compliant in using PPE, and 68.3% were classified as compliant. The results of Spearman correlation test between the motivation of operating room nurses and their compliance in using PPE obtained a correlation coefficient of 0.739 with p equal to 0.000 (p<0.05), thus concluding that operating room nurses' motivation has a significant relationship with their compliance in using PPE. A positive correlation coefficient value can be interpreted that the higher the motivation of operating room nurses, the greater their compliance in using PPE.